Perceptions of Situational Factors of Willingness to Communicate inside and outside the classroom: Thai EFL First-Year University Students' Reflections - Satima Rotjanawongchai (National Research University Higher School of Economics, 2023)
Background: Although previous studies have reported WTC variables in the EFL context, limited studies have investigated learners' perceptions of WTC outside the classroom. In addition, insights into learners' perceptions from qualitative data have rarely been presented in this study area. Purpose: This study investigated the perceptions of willingness to communicate (WTC) of Thai English as a Foreign Language (EFL) first-year university students. It focused on their perceptions of situational factors of WTC inside and outside the classroom. Also, it investigated the reasons behind the perceptions. Methods: As a mixed-method study, a questionnaire adapted from Baghaei's (2013) and Peng and Woodrow's (2010) was used to collect quantitative data, while reflective reports and semi-structured interviews were used to reveal explanations for the quantitative data. Results: The present study found that the students were more willing to speak outside the classroom than inside the classroom. Interlocutors were significant factors affecting WTC both inside and outside the classroom. Also, speaking topics that are suitable for students' perceived level of proficiency but still pose a challenge for their language development have the potential to increase WTC in the classroom.  At the same time, a stimulating environment was powerful for WTC outside the classroom due to a lack of an English-speaking environment in the EFL context. The qualitative data revealed that foreign language anxiety concerning the interlocutor's competence, familiarity with the interlocutor, and language classroom experiences, as well as social support from friends, were the rationale behind the impact of the situational factors. Conclusion: Teachers can apply the results of this present study to enhance WTC in the classroom and increase students' opportunities to speak inside and outside the classroom through pedagogical support.